Effects of hydroalcoholic extract of Borago officinalis on naloxone-precipitated withdrawal syndrome in morphine-dependent mice - Rabiei, Zahra; Lorigooini, Zahra; Kopaei, Mahmoud Rafieian (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to investigate the effect of hydroalcoholic extract of Borago officinalis on morphine withdrawal syndrome in mice. Morphine-dependent group received morphine for nine days and then received naloxone via intraperitoneal injection. Control group received saline for nine days. Post-treated group received B. officinalis extract intraperitoneally (100 mg/kg) on the day 10 before naloxone injection. Co-treated group received B. officinalis extract intraperitoneally (100 mg/kg) and morphine for nine days and then received naloxone. Extract-treated group received extract for nine days and then received naloxone. Naloxone injection significantly increased the frequency of jumping, blinking, ptosis, defecation, paw trembling, and two-legged standing in comparison to the control group. Co-treatment and post-treatment with B. officinalis extract significantly decreased the withdrawal symptoms. In conclusion, hydroalcoholic extract of B. officinalis significantly attenuated the symptoms of morphine withdrawal syndrome. Video Clip of Methodology: 8 min 11 sec Full Screen Alternative